Komparasi daerah sukses dan gagal pasca pemekaran daerah (Studi kasus: Desa Watu Omok dan Papua): Comparison of success and failure regions after regional expansion (Case study: Watu Omok Village and Papua) - Siregar, Tya Efrinamasya Sendhe; Ayu Pebrianti; Lia Ulvi Miranata Putri; Novi Winarti (JOURNAL OF GOVERNMENT SCIENCE, 2024)
Regional development is an attempt to expand the territory of the state administration with the aim of improving public service, economic development, and the well-being of the people. However, the reconstruction of the area carried out for the welfare of this community has not succeeded; in fact, it remains an area that has eventually suffered post-construction failure. This research uses qualitative research methods with a library study approach. As for the area that succeeded in post-development, it was the village of Watu Omok, which saw some improvement. It's because of the support of the public and the government, compliance with conditions, SDA, and even development. Meanwhile, Papua has become a potentially unsuccessful region due to a lack of regional fulfillment. Its causes are financial immaturity and governance, rapid and insufficient formation of aspirations, and a burden on the interests of the political elite.